Expectant versus active management of small for gestational age pregnancies with normal Doppler parameters: an observational study - Byreddy, Srinavya; John, Lopamudra B.; D., Suriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: A successful pregnancy depends on the foetus developing normally, which in turn impacts the foetal health in future. While 70% of small for gestational age (SGA) babies are naturally small and safe, 30% are abnormally little and have a lesser kind of fetal growth restriction (FGR) when their Doppler measurements are normal. Despite normal Doppler at 37 weeks, clinicians often induce all SGA pregnancies, which increases the risk of iatrogenic preterm delivery and surgical treatments. The aim of this study was to assess pregnancy outcome of expectant and active management of small for gestational age pregnancies with normal Doppler parameters. Methods: Study included pregnant women diagnosed as small for gestational age pregnancy with normal Doppler parameters between 28 and 39weeks. The study population (n=60) were divided into two groups- Group 1- Expectant management: To wait up to 39weeks for spontaneous onset of labor, if not induction at 39 weeks. Group 2 - Active management: Induction of labor at 37weeks of gestation. All study participants were followed until delivery. Maternal parameters like onset of labour, Mode of delivery were studied, fetal and neonatal parameters like Apgar score, birth weight and NICU admission were studied. Results: Group 1 expectantly managed group had more spontaneous onset of labour compared to Group 2 which was statistically significant and higher birth weight, more vaginal deliveries and lesser NICU admissions were noted in group 1 compared to group 2. Conclusions: We concluded that SGA pregnancies with normal Doppler parameters may be considered for elective induction at a later date for better maternal and fetal outcomes.